Pengaruh Keamanan Pengemudi dan Ketepatan Waktu Terhadap Kepuasan Pengguna Gojek di Medan - Salsabilla, Hana; Solana Sembiring, Honesty Paskaria; Gloria Manulang, Stefany; Nehe, Janes Alfredo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of driver safety and timeliness on user satisfaction with Gojek services in Medan City. The rapid growth of online transportation services requires companies to maintain service quality in order to achieve and sustain customer satisfaction. Driver safety and service timeliness are two crucial factors that directly influence users’ experiences during each trip. This research employs a quantitative approach with a descriptive method. The data were analyzed using validity tests, reliability tests, and multiple linear regression analysis with statistical software. The results indicate that driver safety and timeliness have a positive and significant effect on Gojek user satisfaction, both partially and simultaneously. These findings suggest that higher levels of driver safety and service timeliness lead to increased user satisfaction. This study is expected to provide practical insights for Gojek in improving service quality, particularly in terms of safety and punctuality, to enhance and maintain customer satisfaction..